Keratinocyte EGF signalling dominates in atopic dermatitis lesions: A comparative RNAseq analysis. Issue 9 (15th May 2022) - Timms, Kate; Guo, Hui; Arkwright, Peter; Pennock, Joanne
Abstract: Atopic dermatitis (AD) remains a highly heterogenous disorder with a multifactorial aetiology. Whilst keratinocytes are known to play a fundamental role in AD, their contribution to the overall immune landscape in moderate‐to‐severe AD is still poorly understood. In order to design new therapeutics, further investigation is needed into common disease pathways at the molecular level. We used publicly available whole‐tissue RNAseq data (4 studies) and single‐cell RNAseq keratinocyte data to identify genes/pathways that are involved in keratinocyte responses in AD and after dupilumab treatment. Transcripts present in both keratinocytes (single‐cell) and whole‐tissue, referred to as the keratinocyte‐enriched lesional skin (KELS) genes, were analysed using functional/pathway analysis. Following statistical testing, 2049 genes (16.8%) were differentially expressed in KELS. Enrichment analyses predicted increases in not only type‐1/type‐2 immune signalling and chemoattraction, but also in EGF‐dominated growth factor signalling. We identified complex crosstalk between keratinocytes and immune cells involving a dominant EGF family signature which converges on keratinocytes with potential immunomodulatory and chemotaxis‐promoting consequences. Although keratinocytes express the IL4R, we observed no change in EGF signalling in KELS after three‐month treatment with dupilumab, indicating that this pathway is not modulated by dupilumab immunotherapy. EGF family signalling is significantly dysregulated in AD lesions but is not associated with keratinocyte proliferation. EGF signalling pathways in AD require further study. Abstract : We have used RNAseq comparative analysis to demonstrate specific crosstalk between immune cells and lesional keratinocytes (KELS) from atopic dermatitis patients. We show for the first time that the KELS transcriptome is dominated by EGF family receptors and downstream signalling alongside the response to type‐1 and type‐2 cytokines.